Kajian Manajemen Produksi Konten Tiktok Non-Asusila Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik (Pasal 27 Ayat (1) Undang-Undang Nomor 19 Tahun 2016) - Rahmat Dwi Putranto; Agnes Harvelian (Neolectura, 2021)
The mode of operation, especially in criminal cases of sexual violence, has apparently also developed following advances in information technology. In writing this journal, the author uses a research method with a descriptive type of analysis. The author emphasizes and tries to answer in detail the study of the production management of non-immoral TikTok content based on UU ITE (Article 27 paragraph 1 of Law Number 19 of 2016). After collecting secondary data, the authors analyzed the results of the study using a qualitative descriptive method. Based on the results of the author's analysis of the data obtained, the writer can conclude that decency is an act or behavior that does not need to embarrass someone when other people see it or know about it, and also because other people are usually not surprised when they see it or find it. Apart from that, there are also things that we need to know when it comes to eradicating immoral crimes in cyberspace. It turns out that the government only cares about making rules and does not explain what is regulated. Therefore, to avoid additional immoral violations, especially in electronic media, Tiktok content must also be non-immoral. There are four stages in the production of non-immoral TikTok content: pre-production planning, setup and rehearsal, production, and post-production. Furthermore, there are four management functions in the production stage as well, namely the planning stage, the organizing stage, the implementation stage, and the monitoring stage.